Efektivitas Pembelajaran Matematika Berbasis E-Learning Pada Materi Sistem Persamaan Linear Dua Variabel Kelas VIII di MTsN 1 Mataram - Ulia Safitri; Baidowi Baidowi; Wahidaturrahmi; Nani Kurniati (Griya Journal of Mathematics Education and Application, 2021)
The purpose of this study was to determine the effectiveness of e-learning based mathematics learning on the material of the two-variable linear equation system for class VIII at MTsN 1 Mataram. This type of research is a descriptive study using a quantitative approach. The research design used a post-test-only control design. All students of class VIII at MTsN 1 Mataram were the population and the sampling technique used cluster random sampling. The sample used was class VIII-8 and VIII-9 who were a member of one sample group. The data in the study were analyzed using descriptive statistics and paired sample t-test to determine whether or not e-learning based mathematic learning was effective in the material of the two-variable linear equation system. Based on the results of data analysis, it is known that e-learning-based mathematics learning with learning video is effectively applied to the material of the two-variable linear equation system for class VIII students at MTsN 1 Mataram the academic year 2020/2021.